Audit: An Important Link in the Modern Management and Control System - Asadova Gulrux (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article highlights the concept of audit, its types, functions, and significance in modern society. Audit is considered an important tool in evaluating the legality, financial condition, and efficiency of an organization’s activities. The article also analyzes the specific features of internal and external audit.